PENYESUAIAN DIRI DAN DUKUNGAN SOSIAL SUAMI DENGAN BABY BLUES SYNDROME PADA IBU PRIMIPARA - Imaniar Astrisari Putri; Puri Aquarisnawati; Fauziah Julike Patrika (Jurnal Psikologi Poseidon, 2022)
Childbirth are usually eager to take care of their babies, but some mothers don’t manage to adjust and experience psychological disorders. The purpose of this study was to determine the relationship between self-adjustment and husband's social support with BBS in primipara mothers. The research used correlational quantitative. Respondents in this study were 40 childbirth to primipara. The sampling technique used saturated sampling. The results show there is a strong relationship between self-adjustment and husband's social support with BBS in primipara mothers. There is a strong relationship between self-adjustment and husband's social support with BBS in primipara mothers. This research shows the importance of preparation for mothers who have just given birth. Husbands also play an important role for mothers who have just given birth and need to provide support in the form of attention and support for assistance.